Ag implantation-induced modification of Ni–Ti shape memory alloy thin films. Issue 7 (3rd August 2017) - Kumar, V.; Singhal, R.; Vishnoi, R.; Banerjee, M.K.; Sharma, M.C.; Asokan, K.; Kumar, M.
ABSTRACT: Nanocrystalline thin films of Ni–Ti shape memory alloy are deposited on an Si substrate by the DC-magnetron co-sputtering technique and 120 keV Ag ions are implanted at different fluences. The thickness and composition of the pristine films are determined by Rutherford Backscattering Spectrometry (RBS). X-Ray diffraction (XRD), atomic force microscopy (AFM) and four-point probe resistivity methods have been used to study the structural, morphological and electrical transport properties. XRD analysis has revealed the existence of martensitic and austenite phases in the pristine film and also evidenced the structural changes in Ag-implanted Ni–Ti films at different fluences. AFM studies have revealed that surface roughness and grain size of Ni–Ti films have decreased with an increase in ion fluence. The modifications in the mechanical behaviour of implanted Ni–Ti films w.r.t pristine film is determined by using a Nano-indentation tester at room temperature. Higher hardness and the ratio of higher hardness ( H ) to elastic modulus ( Er ) are observed for the film implanted at an optimized fluence of 9 × 10 15 ions/cm 2 . This improvement in mechanical behaviour could be understood in terms of grain refinement and dislocation induced by the Ag ion implantation in the Ni–Ti thin films.